2016
DOI: 10.1177/1550059415621830
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Sequential Administration of Melatonin, Hydroxyzine, and Chloral Hydrate for Recording Sleep EEGs in Children

Abstract: Sedation of children for electroencephalography (EEG) recordings is often required. Chloral hydrate (CH) requires medical clearance and continuous monitoring. To try to reduce personnel and time resources associated with CH administration, a new sedation policy was formulated. This study included all children who underwent an EEG during a consecutive 3-month period following the implementation of the new sedation policy, which consists of the sequential administration of melatonin, hydroxyzine (if needed), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 35 publications
4
25
0
Order By: Relevance
“…The induced sleep took effect rapidly and lasted long enough to permit electrode application or recording of sleep or both. There was no report of any immediate or later complications; this was similar to experiences in other centres [16,18]. Wassmer et al [10,13] also did not report any side effects, while Eisermann et al [22] and Milstein [26] reported increased sleepiness in a minority of their subjects.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The induced sleep took effect rapidly and lasted long enough to permit electrode application or recording of sleep or both. There was no report of any immediate or later complications; this was similar to experiences in other centres [16,18]. Wassmer et al [10,13] also did not report any side effects, while Eisermann et al [22] and Milstein [26] reported increased sleepiness in a minority of their subjects.…”
Section: Discussionsupporting
confidence: 74%
“…This study supported that melatonin is effective for attaining sleep EEG recordings in our setting. 86% of the children were achieved stage 2 sleep which is within the range of 75-90% reported in the literature (Table 4) [8,10,[13][14][15][16][17][18] Melatonin has become increasingly popular as a sleep-inducer for both children and adults and has been found to be effective even among children with neurological abnormalities [19][20][21].Among neurophysiology units worldwide, there have been reports of its effectiveness in inducing sleep for EEG and the fact that it does not affect the sleep structure or the epileptiform discharges (Table 4) [8][9][10][16][17][18]22,23].…”
Section: Discussionsupporting
confidence: 71%
“…11,12 Another paper also indirectly reflected the usefulness of melatonin by concluding that they reduced the use of chloral hydrate to obtain a sleep EEG in children by 30% with the sequential administration of melatonin and hydroxyzine before chloral hydrate. 13 The reported side effects of melatonin were minimal across all studies and there were even less behavioural disturbances when compared with sleep deprivation. 14 All these features suggested melatonin is an appropriate choice of sedative agent in EEGs.…”
Section: [ ( F I G _ 4 ) T D $ F I G ]mentioning
confidence: 89%
“…3 Melatonin as an alternative to sedation in children undergoing sleep EEG recording has been reported to be highly efficacious by a few recent studies. 4,5 Various parameters like time to sleep onset and duration of sleep with melatonin administration were found to be similar to that with chloral hydrate. 4 Another study reported shorter sleep duration and drowsiness period with melatonin as compared with chloral hydrate.…”
mentioning
confidence: 77%
“…4,5 Various parameters like time to sleep onset and duration of sleep with melatonin administration were found to be similar to that with chloral hydrate. 4 Another study reported shorter sleep duration and drowsiness period with melatonin as compared with chloral hydrate. 5 However, none of these studies have objectively looked into quality of EEG recordings (yield of EEGs in detecting epileptiform discharges with and without use of melatonin in same subjects) obtained while using melatonin for sedation.…”
mentioning
confidence: 77%